ANALISIS PENENTUAN HARGA POKOK PENJUALAN MENGGUNAKAN METODE FULL COSTING PADA USAHA PABRIK TEMPE DAN TAHU BUANA DI SE’PON KECAMATAN MAKALE KABUPATEN TANA TORAJA - Jein; Helba Rundupadang; Mey E. Limbongan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to determine the calculation of the cost of goods manufactured (COGS) using the full costing method at the Buana Tofu and Tempeh Factory in Se'pon, Makale District, Tana Toraja Regency. The research method used was descriptive with a quantitative approach. Data were obtained through observation, interviews, and documentation related to production costs, including raw material costs, direct labor costs, and fixed and variable factory overhead costs. The results showed that the total production cost of tofu for one year was Rp466,483,000 with a production volume of 1,050,500 pieces, while the total production cost of tempeh was Rp290,217,000 with a production volume of 98,550 packages. Based on calculations using the full costing method, the unit cost of production for tofu was Rp444 per piece and for tempeh was Rp2,945 per package. This calculation demonstrates that the full costing method provides more accurate production cost information because it comprehensively considers all cost components. By accurately knowing the COGS, businesses can determine appropriate selling prices to achieve optimal profits and assist in managerial decision-making and production cost control.